A complete case of Cantrell's Pentalogy with isolated left ventricular diverticulum - Basgoze, Serdar; Ogunc, Begum; Erek, Ersin (CAMBRIDGE UNIV PRESS, 2021)
The congenital left ventricular diverticulum is a rare cardiac malformation, and it may associate with Cantrell's Pentalogy with other cardiac defects. However, isolated ventricular diverticulum without any other cardiac defect in complete Cantrell's syndrome is very rare. We describe a 6-year-old male patient with a complete Cantrell's syndrome with isolated left ventricular diverticulum.
Keywords: Cardiac diverticulum; Cantrell's syndrome; CHD